The Global Quest for Sustainability The Role of Green Infrastructure in a Post-Pandemic World - Secchi, Carlo (ISPI Publications, 2021)
In the aftermath of the pandemic, global demand for infrastructure is booming. National plans around the world show that infrastructure is likely to provide the backbone for a resurgence in public expenditure, and to support growth in economies badly hit by the pandemic. As all the biggest powers and blocs (the EU, the US, China, and Japan) have recently announced their plans for climate or carbon neutrality, the room and need for green and sustainable infrastucture are greatly expanding. Decarbonisation and digitalisation will be underpinning this latest investment drive in infrastructure, with sustainability and ESG principles at its core. However, infrastructure expenditure will not come without risk: after the pandemic, the world will be left with the highest levels of public and private debt since World War II, and the sustainability of key investment decisions must be carefully evaluated. How to foster quality and sustainable infrastructure investment? What role for the private sector? What future for sustainable mobility? What kind of policies will countries adopt to reach carbon neutrality?